New Advances in Kidney Transplantation - Mor, Eytan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue in renal transplantation covers a variety of clinical and research areas in kidney transplantation. The recent decade is associated with an ongoing shortage of organs for transplantation with efforts to increase the organ pool with DCDs and extended criteria donors. However, with the increasing success rate of kidney transplants, there is also a growth in the candidate list because of removal of the age barrier and transplantation of high risk patients with other comorbidities. The future seems promising with the development of innovative non-invasive technologies introducing biomarkers for diagnosis of rejection and ischemic reperfusion injury, use of cell therapy for tolerance induction, development of artificial organs, and overcoming immune and non-immune barriers in xenotransplantation. This Special Issue will touch some of these topics that are in the frontiers of the modern era of kidney transplantation.